2018
DOI: 10.1002/ecm.1287
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic and biotic predictors of macroecological patterns in bird and butterfly coloration

Abstract: Animal color phenotypes are invariably influenced by both their biotic community and the abiotic environments. A host of hypotheses have been proposed for how variables such as solar radiation, habitat shadiness, primary productivity, temperature, rainfall, and community diversity might affect animal color traits. However, while individual factors have been linked to coloration in specific contexts, little is known about which factors are most important across broad taxonomic and geographic scales. Using data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
47
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 85 publications
(237 reference statements)
3
47
0
2
Order By: Relevance
“…These global patterns are in general agreement with recent work on Australian birds both at the species and assemblage levels, which showed similar negative precipitation effects and positive temperature effects (Friedman & Remeš ; Dalrymple et al . ; Delhey ). However, some of these effects vary in strength depending on the specific region (Dalrymple et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These global patterns are in general agreement with recent work on Australian birds both at the species and assemblage levels, which showed similar negative precipitation effects and positive temperature effects (Friedman & Remeš ; Dalrymple et al . ; Delhey ). However, some of these effects vary in strength depending on the specific region (Dalrymple et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, some of these effects vary in strength depending on the specific region (Dalrymple et al . ; Delhey ) or taxonomic group assessed (Friedman & Remeš ). Similarly, work on Spanish birds also reported a positive correlation between plumage lightness and temperature, but not with rainfall (Galván et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here we have deliberately focused on the 389 two climatic variables that are most closely linked to the original ecogeographical rules. However, 390 other climatic (and non-climatic) variables may be playing additional roles (Dalrymple et al 2018) 391 and correlations with temperature and precipitation may be driven by other causes. For example, it 392 has been suggested that Gloger's rule should be reformulated in terms of vegetation rather than 393 precipitation because the former is presumably more closely linked to the putative mechanism 394 (darker animals more camouflaged in darker environments) (Zink & Remsen 1986).…”
Section: Discussion 279mentioning
confidence: 99%